ICTS INSTRUCTIONAL COMPETENCIES POSSESSED BY LECTURERS FOR IMPLEMENTING OTM CURRICULUM IN PUBLIC TERTIARY INSTITUTIONS IN RIVERS STATE (NAU Journal of Technology and Vocational Education, 2024)
In the recent times, implementation of office technology and management (OTM) curriculumlargely depends on ICTs instructional competencies. Therefore, this study determined the levelof ICT instructional competencies possessed by lecturers for implementing OTM curriculum inpublic tertiary institutions in Rivers State. One research question guided the study and three nullhypotheses were tested. Descriptive survey research design was adopted. From a population of69 OTM lecturers, the census survey sampling was employed. A five-point response optionsquestionnaire was used for data collection, and it was validated by expert. The reliability of theinstrument was established using Cronbach’s alpha which yielded a alpha coefficient of 0.93.Mean was used to answer the research question, while one-way analysis of variance (ANOVA)and t-test were used to test the null hypotheses at 0.05 level of significance. Findings revealedthat the lecturers possessed ICTs instructional competencies at a high level for the implementingOTM curriculum. The lectures do not differ significantly in the level they possessed ICTscompetencies for OTM curriculum implementation based on their level of education, teachingexperience and institution ownership. Therefore, it was recommended that OTM lecturers shouldconciously engage in further ICTs trainings to sustain and improve their ICTs instructionalcompetencies for effective curriculum implementation in their areas of operations.
Keywords: ICTs, instructional competencies, lecturers, curriculum implementation, public tertiary institutions